Grau de liberação de diferentes tipos de minério de ferro das Minas de Alegria (Mariana-MG) e sua influência nas etapas de cominuição e concentração - Rafael de Souza Rodrigues (2016)
The mineral liberation, obtained from reducing the particle size by grinding, is one of the basic concepts for the flotation process. Only the quantification of the liberation degree of quartz does not provide the necessary information for predictability in the flotation process. The characterization of mineral liberation, using complementary techniques such as optical microscopy and MLA, the qualitative analysis of mixedparticles considering the different proportions of the constituent phases of these particles and mineralogical associations, detailing the distribution of the types of free and mixed particles, are some of the basic information for understanding the ores behavior during comminution and concentration processes. The purpose of this work was to study the mineral liberation of five different types of itabirites, to the determineand understand the influence of the mineral liberation in different degrees of comminution and to assess the distribution of the mixed particles after the flotation process. The studied itabirites types showed different behaviors in the grinding process. The samples AGEO88 and AGEO91 showed liberation of quartz higher than 98% and the percentage of mixed particles smaller than 10% after five minutes grinding. The samples AGEO72, AGEO77 and AGEO 107 only showed reasonable mineral liberation after twenty minutes grinding. At the end of grinding, the sample AGEO72 presented a 90.2% liberation degree of quartz, with 26% of mixed particles remaining; the sample AGEO77 with only 71.5% degree of liberation of quartz showed 49% of mixed particles and the sample AGEO107 presented 88.7% degree of liberation quartz with 21% of mixed particles. After the desliming stage, the samples were subjected to mineralogical characterization for studying the conditions for mineralliberation in the flotation process. In agreement with the data obtained in the grinding stage, the samples AGEO88 and AGEO91 showed excellent conditions of mineral liberation, completely favorable to the flotation process with a high degree of quartz liberation and the majority of particles (quartz and iron oxides and hydroxide) liberated. The remaining samples, AGEO72, AGEO77 and AGEO107 showed mineral liberation conditions unfavorable for the flotation process, with quartz liberation degrees of 89%, 78.6% and 88.6%, respectively, and relevant proportion of mixed particles (>29%). The flotation performance of the AGEO88 sample was excellent, with an iron concentrate having only 0.79% SiO2 content and the metallurgical recovery close to 89%. For the samples that showed inadequate mineral liberation conditions, the iron concentrates obtained had unsatisfactory quality with SiO2 content of 3.71% for AGEO72, 14.03% for AGEO77 and 3.35% for AGEO107. The iron contents in the tailings from these samples were above 20% and the metallurgical recovery less than 65%. Amazing was the performance of AGEO 91, which frustrated all expectations, with SiO2 content in the concentrate equal to 18.2% and 24.3% iron content in the tailings. The sample with the worst iron concentrate quality among the studied samples, showed excellent mineral liberation degree, however, some other factor have contributed negatively upon the selectivity in the flotation process. The mineralogical characterization of various types of itabirites focusing on the mineral liberation provided important information for understanding the behavior in the grinding and flotation processes, which contributes strongly to predictability, one of the pillars in the development of a geometallurgical model.